INDUSTRY 4.0 INTEGRATION WITH SAP S/4HANA FOR RESPONSIVE PRODUCTION - BANȚA VIOREL COSTIN; NECULA ADINA-THEODORA; TĂNASE ANDREEA GABRIELA; MĂLDĂREANU ANDREEA; CREȚU RALUCA-FLORENTINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This study examines the integration of Industry 4.0 tools within SAP S/4HANA to improve production responsiveness. While traditional SAP ECC setups lack these integrations, S/4HANA enables the adoption of advanced technologies. The core research question is: 'How does Industry 4.0 integration impact production responsiveness in SAP S/4HANA?' We hypothesize that combining Industry 4.0 tools with S/4HANA fosters greater adaptability to production demands. The methodology includes case studies comparing SAP ECC and S/4HANA implementations, with a focus on real-time responsiveness. The expected results show improved agility and reduced response times in production settings. Management insights will detail the strategic benefits of Industry 4.0 for production leaders. This research highlights the adaptability advantages gained through digital transformation with S/4HANA. The findings underline the competitive advantage Industry 4.0 brings to modern ERP environments.